New synthetic strategies for xanthene-dye-appended cyclodextrins - Malanga, Milo; Darcsi, Andras; Balint, Mihaly; Benkovics, Gabor; Sohajda, Tamas; Beni, Szabolcs (Beilstein Journal of Organic Chemistry, 2016)
Xanthene dyes can be appended to cyclodextrins via an ester or amide bridge in order to switch the fluorescence on or off. This is made possible through the formation of nonfluorescent lactones or lactams as the fluorophore can reversibly cyclize. In this context we report a green approach for the synthesis of switchable xanthene-dye-appended cyclodextrins based on the coupling agent 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMT-MM). By using 6-monoamino-β-cyclodextrin and commercially available inexpensive dyes, we prepared rhodamine- and fluorescein-appended cyclodextrins. The compounds were characterized by NMR and IR spectroscopy and MS spectrometry, their UV–vis spectra were recorded at various pH, and their purity was determined by capillary electrophoresis. Two potential models for the supramolecular assembly of the xanthene-dye-appended cyclodextrins were developed based on the set of data collected by the extensive NMR characterization.
Keywords: DMT-MM; fluorescein; rhodamine; supramolecular assembly